Construction of educational products on the rational use of medicines (Research, Society and Development, 2021)
This article aims to report the experience of building educational products capable of informing users and health professionals about the Rational Use of Medicines, through a descriptive study, with a qualitative approach, of the experience report type, resulting from the production of the Professional Master's Degree in Education in Health and Technology at a Higher Education Institution in Alagoas. The construction of educational health products is one of the teaching strategies used throughout the course. A series of three videos on the Rational Use of Medicines was created. The elaboration process of these educational products was based on the CTM3 method, through which the following tools were explored: Transactional Analysis, Sensory Exploration and Neurolinguistics. Video as a teaching tool is a didactic tool that encourages more accessible and easily communicated education. Thus, it is concluded that, in the production of educational products in health, skills, competences and recognition of social needs are essential, as is the use of information and communication technologies in the most diverse ways. The Rational Use of Medicines is a relevant topic and lacks wide dissemination.